1983
DOI: 10.1159/000137900
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Comparison of Suprofen and Propoxyphene in Patients with Osteoarthritis

Abstract: The analgesic efficacy and safety of suprofen, 200 mg q.i.d., and propoxyphene, 65 mg q.i.d., were compared in 114 patients with chronic pain due to osteoarthritis. Both analgesic agents decreased pain intensity after only 1 week of treatment and considerable pain relief was apparent by week 2 to week 3 of treatment. These beneficial effects persisted with long-term therapy and improvement continued throughout the 24-week treatment period. Overall, the response to suprofen and propoxyphene was good to excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Of the 43 studies, 40 (93%) provided efficacy data 29–68 . One of the 40 treatment studies 58 also provided information on rates of abuse and misuse, whereas three provided data only on rates of abuse and misuse 69–71 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 43 studies, 40 (93%) provided efficacy data 29–68 . One of the 40 treatment studies 58 also provided information on rates of abuse and misuse, whereas three provided data only on rates of abuse and misuse 69–71 .…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies compared opioid therapy with another active treatment (a nonsteroidal anti‐inflammatory or a tricyclic antidepressant) 42,55,64 . One found a nonsignificant difference in level of neuropathic pain reduction (effect size 0.206) between long‐acting morphine and tricyclic antidepressant (nortriptyline or desipramine) therapy 64 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 79 original references, 12 were excluded through the above exclusion criteria. The remaining 67 reports [1–3,5–12,14–22,27,37,40–44,50–89] were reviewed in detail. It is to be noted that some studies addressed more than one issue relating to this review.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its potential for adverse effects, the clinical efficacy of propoxyphene has also been debated. Several studies have demonstrated that propoxyphene is no more effective than acetaminophen, aspirin, codeine, or ibuprofen in reducing pain and may even be inferior 8–12 . Another study could not establish significant therapeutic effectiveness for propoxyphene 13 .…”
mentioning
confidence: 99%